Kewenangan Kepala Dinas Kesehatan Kota Surabaya dalam Pengawasan Rumah Sakit - Katarina, Katarina; Noor, Tauchid; Asmuni, Asmuni (Syntax Corporation, 2025)
The rise in cases of medical disputes involving hospitals makes it important to monitor health provider internally and externally to ensure hospital quality assurance and to protect the community from all possible causes that could pose a danger to public health, as well as providing legal certainty to the community and hospital management. This research analyzes the authority of Surabaya City Health Service in carrying out law enforcement if there are any findings in hospital supervision and also analyzes what obstacles arise in hospital monitoring throughout Surabaya City. The research methodology used in writing thesis is normative juridical and the research approach uses a statute approach and a conceptual approach. This research concludes that The Law on Health gives authority to Regional Governments to supervise every implementation of health services, while PP No. 28 of 2024 gives authority to Regional Government to monitor and evaluate hospitals, but law enforcement authority is only given to the Central Government in the form of imposing administrative sanctions. Obstacle arise in hospital supervision activity include the lack of technical instruction for implementing norms, standards, procedures, and criteria so that scoring model for supervision of hospital business licensing through the OSS system cannot be implemented..